Serine and alanine racemase activities of VanT: A protein necessary for vancomycin resistance in Enterococcus gallinarum BM4174 (2000)
Vancomycin resistance in Enterococcus gallinarum results from the production of UDP-MurNAc-pentapeptide[D-Ser]. VanT, a membrane-bound serine racemase, is one of three proteins essential for this resistance. To investigate the selectivity of racemization of L-Ser or L-Ala by VanT, a strain of Escherichia coli TKL-10 that requires D-Ala for growth at 42 °C was used as host for transformation experiments using plasmids containing the full-length vanT from Ent. gallinarum or the alanine racemase gene (alr) of Bacillus stearothermophilus: both plasmids were able to complement E. coli TKL-10 at 42 °C. No alanine or serine racemase activities were detected in the host strain E. coli TKL-10 grown at 30, 34 or 37 °C. Serine and alanine racemase activities were found almost exclusively (96%) in the membrane fraction of E. coli TKL-10/pCA4(vanT): the alanine racemase activity of VanT was 14% of the serine racemase activity in both E. coli TKL-10/pCA4(vanT) and E. coli XL-1 Blue/pCA4(vanT). Alanine racemase activity was present mainly (95%) in the cytoplasmic fraction of E. coli TKL-10/pJW40(alr), with a trace (1·6%) of serine racemase activity. Additionally, DNA encoding the soluble domain of VanT was cloned and expressed in E. coli M15 as a His-tagged polypeptide and purified: this polypeptide also exhibited both serine and alanine racemase activities; the latter was approximately 18% of the serine racemase activity, similar to that of the full-length, membrane-bound enzyme. N-terminal sequencing of the purified His-tagged polypeptide revealed a single amino acid sequence, indicating that the formation of heterodimers between subunits of His-tagged C-VanT and endogenous alanine racemases from E. coli was unlikely. The authors conclude that the membrane-bound serine racemase VanT also has alanine racemase activity but is able to racemize serine more efficiently than alanine, and that the cytoplasmic domain is responsible for the racemase activity.